The Presence of Scarring and Associated Morbidity in the Burn Model System National Database. (March 2019) - Goverman, Jeremy; He, Waverley; Martello, Geoffrey; Whalen, Ann; Bittner, Edward; Schulz, John; Gibran, Nicole; Herndon, David; Suman, Oscar; Kowalske, Karen; Meyer, Walter J.; Ryan, Colleen; et al.
Abstract : Introduction: Postburn scarring is common, but the risk factors, natural history, and consequences of such scars are still poorly understood. This study aims to describe the frequency of scar-related morbidity for up to 2 years after injury and to analyze the impact of burn scars on long-term functional, psychosocial, and reintegration outcomes. Methods: Analysis was conducted on data collected between January 2006 and May 2014 from 960 patients (2440 anatomic burn sites) using the Burn Model System (BMS) database. Study population demographics were analyzed and odds ratios for the development of raised or thick scarring were determined. Regression analyses were used to evaluate the impact of hypertrophic scarring (HTS) on psychosocial outcomes, including the Community Integration Questionnaire, Satisfaction with Life Scale, Distress, and the Short Form 12. Symptoms associated with scarring were analyzed at discharge and 6, 12, and 24 months after burn using a set of questions on scarring developed by the BMS. Mixed-effect modeling was used to determine linear change over time and the significance of symptoms. Results: The study population was primarily white (65.0%) and male (71.8%), with a mean (SD) age of 44.0 (15.2) years and mean total body surface area burned of 19.6% (17.9%). The incidence of raised or thick scars increased from 65% to 80% ( P < 0.0001) for the 2-year follow-up period. The presence of scarring was not associated with Community Integration Questionnaire, Satisfaction with Life Scale, or Short Form 12 scores. Most patients reported symptoms associated with scarring at 2 years after burn, including dry or fragile skin, scars that restrict range of motion at a joint, issues with hand function, and scar pain and itch. Conclusions: In this large, longitudinal, multicenter cohort of burn survivors, nearly all patients noted the presence of scarring, and a majority noted additional symptoms and morbidity related to their scars even at 2 years after injury. This study demonstrates a need for the continued support of burn survivors to address scar-related morbidity. Furthermore, future studies examining the impact of novel treatments for scarring should use similar scar problem questionnaires and distress scores.